Deciphering the complex three-way interaction between the non-integrin laminin receptor, galectin-3 and Neisseria meningitidis - Alqahtani, Fulwah Yahya Saleh; Mahdavi, Jafar; Wheldon, Lee M.; Vassey, Matthew; Pirinccioglu, Necmettin; Royer, Pierre-Joseph; Qarani, Suzan M.; Morroll, Shaun; Stoof, Jeroen; Holliday, Nicholas D.; Teo, Siew Y.; Oldfield, Neil J.; et al. (Royal Society, 2014)
The non-integrin laminin receptor (LAMR1/RPSA) and galectin-3 (Gal-3) are multi-functional host molecules with roles in diverse pathological processes, particularly of infectious or oncogenic origins. Using bimolecular fluorescence complementation and confocal imaging, we demonstrate that the two proteins homo- and heterodimerize, and that each isotype forms a distinct cell surface population. We present evidence that the 37 kDa form of LAMR1 (37LRP) is the precursor of the previously described 67 kDa laminin receptor (67LR), whereas the heterodimer represents an entity that is distinct from this molecule. Site-directed mutagenesis confirmed that the single cysteine (C173) of Gal-3 or lysine (K166) of LAMR1 are critical for heterodimerization. Recombinant Gal-3, expressed in normally Gal-3-deficient N2a cells, dimerized with endogenous LAMR1 and led to a significantly increased number of internalized bacteria (Neisseria meningitidis), confirming the role of Gal-3 in bacterial invasion. Contact-dependent cross-linking determined that, in common with LAMR1, Gal-3 binds the meningococcal secretin PilQ, in addition to the major pilin PilE. This study adds significant new mechanistic insights into the bacterial–host cell interaction by clarifying the nature, role and bacterial ligands of LAMR1 and Gal-3 isotypes during colonization.